Comparing Examination Modes in Finland and Bhutan's Education System and Suggestions for Improvement - Kinley Dorji (International Journal of Qualitative Research, 2023)
This research paper delves into the assessment and examination systems of primary and secondary education in Finland and Bhutan. It analyzes Finland's exceptional performance in PISA and its assessment practices, emphasizing formative assessment and project-based learning. In contrast, Bhutan relies more heavily on standardized exams. The study identifies major similarities and differences, strengths, and weaknesses in both countries' examination modes. It investigates how these variations impact student learning outcomes in each nation. Through a qualitative comparative analysis research design, the paper focuses on exploring the examination methods in Finland and Bhutan's education systems. Based on the findings, the research proposes practical strategies for enhancing Bhutan's examination system. It suggests integrating formative assessment, introducing a blended approach in secondary education, and promoting research-based projects to improve the overall examination methods in Bhutan. While the study may not directly influence policy, it provides valuable insights into Finland's successful practices, which can be adapted to benefit Bhutan's education system.